Quelle histoire pour les quartiers d’architecture étrangère en Chine ? Entrecroisements des récits et des enjeux d’acteurs à Thames Town, en périphérie de Shanghai - Martin Minost (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This contribution aims to analyse the different narratives produced by the actors involved in the social and symbolic construction of the neighborhood of Thames Town, in the new city of Songjiang, a peripheral district of Shanghai. Built between 2002 and 2006, this residential and tourist area has been the subject of numerous analyses and discourses due to the English architectural styles that have been reproduced there. In spite of its relatively recent construction, a rich corpus of historical data therefore has not yet been used to analyze changes in the neighborhood and in the relationships between the various actors.The analysis of the narratives and representations produced by developers, outside observers and daily users reveals reciprocal influences in the perceptions of the neighborhood and the issues that guide each of the parties. Moreover, the analysis of these narratives and their use shows that, contrary to the commonly disseminated representations of a disconnected space within Chinese society, in reality, the district is integrated into multiple histories and trajectories.